CHARACTERISTICS OF ENGLISH GRAMMAR SKILLS IN VARIOUS TYPES OF SPEECH ACTIVITY - Boltaev, Chutkul (Журнал иностранных языков и лингвистики, 2023)
The article gives a characteristic of grammar skills, given their types.